RE-SHAPING THE PROPHET: Baḥr al-Mādhī, Vernacular Fracture and Characteristics of Hadith Commentary in Nusantara - Firdausy, Hilmy (RIWAYAH, 2022)
Baḥr al-Mādhī Syarah Bagi Mukhtasar Sahih al-Tirmidhi by Muhammad Idris al-Marbawi is one of the hadith works of Nusantara scholars, which contains wealthy textual data. It provides 22 chapters divided into 11 volume bundles. However well, not much research has touched on Baḥr al-Mādhī. This paper will specifically reveal the “locality” and distinctive aspects of the hadith commentary scheme in Baḥr al-Mādhī. For this purpose, this paper will use and apply the theory of vernacularization. The theory will record the meeting of “the local” and “ the universal”, which is expected to capture aroma of the Nusantara in the Baḥr al-Mādhī Syarah Bagi Sahih al-Tirmidhi written in Malay language with Pegon script. As a result, at least five methodical characteristics are applied by al-Marbawi in hadith commentary, methods that are never applied by other hadith scholars when observing and explaining the same hadith. The vernacularization or momentum of locality displayed in Baḥr al-Mādhī occurs at once at all its semiotic levels. In the context of the hadith commentary method, there are at least specific characteristics that distinguish Baḥr al-Mādhī from the typical hadith commentary books; 1) visualization of interpretation in the form of drawings and illustrations, 2) utilization of storytelling techniques, 3) the emergence of two-way dialogue and translation spaces, 4) clustering of quotations and 5) the use of pointers.[Baḥr al-Mādhī Syarah Bagi Sahih al-Tirmidhi karya Muhammad Idris al-Marbawi adalah salah satu karya hadis ulama Nusantara yang memuat data tekstual yang sangat kaya. Ia menyediakan 22 juz bahasan yang dibagi ke dalam 11 bundel jilid. Namun sayangnya, tidak banyak penelitian yang menyentuh Baḥr al-Mādhī. Paper ini secara spesifik akan menguak aspek “lokalitas” dan yang khas dalam skema pensyarahan hadis dalam Baḥr al-Mādhī. Untuk kepentingan itu, teori vernakularisasi akan digunakan. Teori tersebut akan merekam pertemuan “yang lokal” dan “yang universal” ini diharapkan mampu memotret aroma kenusantaraan atau “roso jawi” dalam kitab syarah hadis yang ditulis dalam Bahasa Melayu beraksara pegon tersebut. Hasilnya, ada setidaknya lima  karakteristik metodis yang diterapkan oleh al-Marbawi dalam mensyarah hadis; metode-metode yang tidak pernah diterapkan oleh para ulama hadis lainnya ketika mensyarah hadis yang sama. Vernakularisasi atau momentum lokalitas yang ditampilkan dalam Baḥr al-Mādhī terjadi sekaligus pada semua tataran semiotiknya. Dalam konteks metode tafsir hadis, setidaknya ada ciri-ciri khusus yang membedakan Bahr al-Mādhī dengan kitab tafsir hadis pada umumnya; 1) visualisasi interpretasi berupa gambar dan ilustrasi, 2) pemanfaatan teknik bercerita, 3) munculnya dialog dua arah dan ruang penerjemahan, 4) pengelompokan kutipan dan 5) penggunaan pointer.]